Housing affordability and parental income support - Jason Allen; Kyra Carmichael; Robert Clark; Shaoteng Li; Nicolas Vincent (Bank of Canada, 2024)
In many countries, the cost of housing has greatly outpaced income growth, leading to a housing affordability crisis. Leveraging Canadian loan-level data and quasi-experimental variation in payment-to-income constraints, we document an increasing reliance of first-time homebuyers on financial help from their parents, through mortgage co-signing. We show that parental support can effectively relax borrowing constraints-potentially to riskier borrowers.
Keywords: G51; D64; E21; G18; E24; 330; Housing; Financial services; Financial system regulation and policies